Rosemary Aromatization of Extra Virgin Olive Oil and Process Optimization Including Antioxidant Potential and Yield - Erkan Karacabey; Gulcan Özkan; Latife Dalgıç; Saliha Onur Sermet (Turkish Journal of Agriculture: Food Science and Technology)
Aromatization of olive oil especially by spices and herbs has been widely used technique throughout the ages in Mediterranean diets. The present study was focused on aromatization of olive oil by rosemary (Rosmarinus officinalis L.). Aromatization process was optimized by response surface methodology as a function of malaxation’s conditions (temperature and time). According to authors’ best knowledge it was first time for examination of oil yield performance with antioxidant potential and pigments under effect of aromatization parameters. For all oil samples, values of the free acidity, peroxide, K232 and K270 as quality parameters fell within the ranges established for the highest quality category “extra virgin oil”. Oil yield (mL oil/kg olive paste) changed from 158 to 208 with respect to design parameters. Total phenolic content and free radical scavenging activity as antioxidant potential of olive oil samples were varied in the range of 182.44 – 348.65 mg gallic acid equivalent/kg oil and 28.91 – 88.75 % inhibition of 2,2-Diphenyl-1-picrylhydrazyl-(DPPH•), respectively. Total contents of carotenoid, chlorophyll and pheophytin a as pigments in oil samples were found to be in between 0.09 – 0.48 mg carotenoid/kg oil, 0.11 – 0.96 mg chlorophyll/kg oil, 0.15 – 4.44 mg pheo α/kg oil, respectively. The proposed models for yield, pigments and antioxidant potential responses were found to be good enough for successful prediction of experimental results. Total phenolics, carotenoids and free radical scavenging activity of aromatized olive oil and oil yield were maximized to gather and optimal conditions were determined as 25°C, 84 min, and 2 % (Rosemary/olive paste; w/w).